2017
DOI: 10.3758/s13423-017-1269-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of memory for melodies: Articulation or attentional refreshing?

Abstract: Past research on the effects of articulatory suppression on working memory for nonverbal sounds has been characterized by discrepant findings, which suggests that multiple mechanisms may be involved in the rehearsal of nonverbal sounds. In two experiments we examined the potential roles of two theoretical mechanisms of verbal working memory-articulatory rehearsal and attentional refreshing-in the maintenance of memory for short melodies. In both experiments, participants performed a same-different melody compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
4
12
0
1
Order By: Relevance
“…Taken together, the results suggested that subvocal articulatory rehearsal plays a role in working memory for nonverbal sounds discriminable only by timbre, whereas attentional refreshing does not. The results mirrored the pattern of findings for memory for melodies reported in Nees, Corrini, et al (2017), which lends some support to the hypothesis that pitch and timbre share a rehearsal mechanism in working memory. Across all conditions, the d' scores were relatively low.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Taken together, the results suggested that subvocal articulatory rehearsal plays a role in working memory for nonverbal sounds discriminable only by timbre, whereas attentional refreshing does not. The results mirrored the pattern of findings for memory for melodies reported in Nees, Corrini, et al (2017), which lends some support to the hypothesis that pitch and timbre share a rehearsal mechanism in working memory. Across all conditions, the d' scores were relatively low.…”
Section: Discussionsupporting
confidence: 84%
“…Research to examine the effects of articulatory suppression on nonverbal musical sounds, however, often has shown that articulatory suppression does impair memory for those sounds. For example, across multiple studies, articulatory suppression has been shown to impair memory for melodies (Logie & Edworthy, 1986;Nees, Corrini, Leong, & Harris, 2017;Schendel & Palmer, 2007). Articulatory suppression also has been shown to interfere with other musical tasks that seem to have a nonverbal memory component, including judging the pitch content of recognizable melodies (Smith, Wilson, & Reisberg, 1995) and judging differences between musical notation and heard melodies (Brodsky, Kessler, Rubinstein, Ginsborg, & Henik, 2008).…”
Section: Soundsmentioning
confidence: 99%
See 3 more Smart Citations